2001
DOI: 10.1016/s0370-2693(01)00808-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflation, braneworlds and quintessence

Abstract: Inflationary cosmology is developed in the second Randall-Sundrum braneworld scenario, where the accelerated expansion arises through potentials that are too steep to drive inflation in conventional cosmology. A relationship between the scalar and tensor perturbation spectra is derived that is independent of both the inflaton potential and the brane tension. It is found that a single field with an inverse power law potential can act as both the inflaton and the quintessence field for suitable values of the bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
187
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(199 citation statements)
references
References 57 publications
12
187
0
Order By: Relevance
“…This gives rise to the intriguing possibility that both inflation and quintessence may be sourced by one and the same scalar field. Termed 'quintessential inflation', these models have been examined in [142,53,85,169,116,66,106,57,185,178,177]. An example of quintessential inflation is shown in figure 8.…”
Section: Dark Energy In Braneworld Modelsmentioning
confidence: 99%
“…This gives rise to the intriguing possibility that both inflation and quintessence may be sourced by one and the same scalar field. Termed 'quintessential inflation', these models have been examined in [142,53,85,169,116,66,106,57,185,178,177]. An example of quintessential inflation is shown in figure 8.…”
Section: Dark Energy In Braneworld Modelsmentioning
confidence: 99%
“…This problem arose for the first time when the degeneracy of the 4D and RS lowest-SR-order tensor index was discovered [1,2]; several works then showed that this degeneracy is most likely incidental (e.g. [3] and references therein).…”
Section: Introduction and Setupmentioning
confidence: 99%
“…However, here it should be pointed out that T * is overestimated above because we have considered an instantaneous transition between inflation and kination. In reality this transition takes some time so that t * is somewhat larger and, therefore, T * turns out about an order of magnitude smaller that the estimate of (24) [15]. This will be taken into account when we apply the BBN constraint below.…”
Section: Brane Kinationmentioning
confidence: 99%
“…Moreover, mild quintessential tails, e.g. of the inverse power-law type [15], make it hard to satisfy coincidence. Furthermore, quintessential tails steeper than exponential have disastrous attractors [13], which, not only do they diminish ρ φ faster than ρ B , but are also reached very soon after the end of inflation and, therefore, cannot lead to late-time acceleration.…”
Section: The Hot Big Bangmentioning
confidence: 99%